2015
DOI: 10.9734/ca/2015/15236
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Their Relationship with Leptin and Cardiovascular Risk Factors in Pre and Post-Menopausal Nigerian Women with Metabolic Syndrome

Abstract: Metabolic Syndrome (MS), which affects 33.1% of Nigerians, predisposing them to cardiovascular disease (CVD) risk, has been associated with the female gender. The cardioprotective effect of oestradiol against CVD is now controversial and was investigated in premenopausal with MS (PRMMS) and postmenopausal women with MS (POMMS). A total of 191 women (44 PRMMS, 126 POMMS and 21 premenopausal women without MS (PRM) (controls) with mean (s.d) age of 40.0 (6.9), 57.0 (8.8), 29.0 (6.8) years were participants of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The visceral adipose tissue secretes leptin, an adipocytokine associated with the processes of inflammation, endothelial dysfunction, hypertension and atherogenesis. Increased levels of leptin in cases when compared with controls (P<0.05), observed in this present study has been previously reported (Fabian et al, 2015). DBP had a positive relationship with leptin in the control group only (P<0.05).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The visceral adipose tissue secretes leptin, an adipocytokine associated with the processes of inflammation, endothelial dysfunction, hypertension and atherogenesis. Increased levels of leptin in cases when compared with controls (P<0.05), observed in this present study has been previously reported (Fabian et al, 2015). DBP had a positive relationship with leptin in the control group only (P<0.05).…”
Section: Discussionsupporting
confidence: 85%
“…The increase in FSH levels in the cases compared with the controls (P<0.05) may suggest compensatory hypogonadism in the cases. As women approach menopause, FSH levels fall, ovarian follicular activity decreases, leading to decline in oestrogen level (Fabian et al, 2015). There is the resultant gradual loss of hormonal feedback mechanisms leading to the compensatory elevation of FSH for adequate production of oestradiol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations